Peran Media Sosial dalam Strategi Branding Shane Self Photo Studio di Tengah Kompetitor Melalui Pendekatan Digital Marketing (Jurnal Riset Manajemen dan Akuntansi, 2025)
The photography industry in Gunungsitoli City has experienced rapid growth, marked by the increasing number of photo studios utilizing social media as a means of promotion and brand strengthening. This competition demands that every business owner possess a strong brand identity and an effective digital marketing strategy. Shane Self Photo Studio, despite its strengths in photography quality and customer service, faces challenges in building a consistent brand image on digital platforms. Several competitors have intensively optimized social media, while the studio’s content management remains suboptimal. This study aims to analyze the role of social media in the branding strategy of Shane Self Photo Studio in facing competition in the photography industry. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldana model. The findings indicate that social media, particularly Instagram and Facebook, plays a significant role in increasing the studio’s visibility. However, weaknesses in content strategy consistency, storytelling, and customer interaction serve as major obstacles. The absence of a dedicated digital marketing team also limits promotional effectiveness. Documentation findings reveal that competitors who actively manage social media tend to be more successful in attracting and retaining customers..